PERAN PERILAKU KONSUMEN GENERASI Z DAN KESADARAN LOKAL PADA SOSIAL BUDAYA UNTUK PERILAKU PEMBELIAN (STUDI KASUS SHOPEE) - Alda Pebrianti; Navisa Anindya Riyanto Putri; Muhammada Kosim; Muhammad Raihan Ibrahim; Kania (Jurnal Riset Multidisiplin Edukasi, 2025)
This study comprehensively examines and analyzes the influence of Generation Z consumer behavior and local awareness of socio-cultural aspects on purchasing decisions, using the Shopee e-commerce platform as the main case study. Generation Z, a market segment with increasing purchasing power, exhibits unique consumption characteristics, with preferences that tend to align with social, ethical, and cultural values. These dynamics are often encountered and significantly facilitated through digital environments, particularly e-commerce platforms. The research adopts a qualitative approach, with data collected through structured in-depth interviews with active Generation Z respondents, as well as an analysis of Shopee's platform, which is designed to support and promote local products. The analysis results indicate that Generation Z's level of awareness regarding the social impact of their consumption and the importance of preserving local cultural heritage substantially influences their preferences and ultimately their purchasing decisions. The ease of access, visibility, and promotional mechanisms for local products provided by Shopee are proven to be key driving factors behind this purchasing behavior. Generation Z demonstrates a strong tendency to choose brands or products that not only offer quality but also show a genuine commitment to sustainability practices, principles of fairness, and active efforts in promoting and preserving cultural heritage—values that are often effectively advertised and highlighted within Shopee’s ecosystem. The strategic implications of this study underscore the urgency for businesses and marketers to develop and implement innovative digital marketing strategies that holistically integrate socio-cultural values, especially when engaging with the Gen Z consumer segment through dominant digital platforms like Shopee.